Relationship Between Mother’s Age, Birth Weight and Prematurity With The Incidence of Asphyxia at RSD Mangusada-Bali - Sukmandari, Ni Made Ari; Mey Ani, Ni Luh Putu; Sukriyanti, Putu Ari (Poltekkes Kemenkes Maluku, 2025)
Asphyxia neonatorum is a condition where a baby cannot breathe spontaneously and regularly immediately after birth. One of the causes of asphyxia is the mother's age, prematurity and the baby's birth weight. The aim of this study was to determine the relationship between maternal age, birth weight, prematurity with the incidence of asphyxia. This research is a correlational study with an analytical description design and uses a cross sectional approach. Respondents in this study were 36 respondents who were selected by accidental sampling with inclusion and exclusion criteria. This research instrument used an observation sheet which had previously been tested and the research data was analyzed univariately and bivariately with the Spearman rank test (α = 0.05). The average age of the mother is 31.86 years, the birth weight of the baby is 2,462 grams and the gestational age is 35 weeks with an average APGAR score of 4. The Spearman rank test showed that there was a relationship between maternal age (p value 0.002), birth weight (p value 0.03) and prematurity (0.04) with the incidence of asphyxia at RSD Mangusada. Pregnant women are expected to carry out periodic antenatal care checks and avoid factors inhibiting fetal development during pregnancy.